Varicose veins - Ellis, Harold (Greenwich Medical Media, 1999)
This third edition addresses the aetiology and treatment of varicose veins in plain language. It deals with possible causes, treatment, complications and common questions and answers. The text has been brought up-to-date and includes clear explanations of recently developed diagnostic techniques. The book is fully illustrated throughout to aid understanding.